Development of Vocal Teaching Materials Based on Keroncong Singing Or- naments to Strengthen Western Vocal Technique - Latifah, Diah; Milyartini, Rita (PANGGUNG, 2017)
ABSTRACTThis study develops teaching materials based on âLuk Keroncong Song Ornaments". The method used was designed based research that was developed from teaching materials which were based on the strength of the theoretical and applicative activities to test the strength of materials. The results of the study revealed that the Luk Keroncong ornaments, when it is used, strengthen the vocal technique used by the respondents. The result of this research revealed that the teaching material employed improve the respondentsâ vocal technique. Notable areas of improvement and strengthening of the respondents were observed in their:-breathing management (Appogio), vocal registration, especially when there are changes in the timbre (passaggio), head-voice resonance, flexibility of tone, and stability of tone.Keywords: Instructional material based on luk keroncong ornament, Implementation, Strengthening, Vocal TechniquesÂ